Program Makan Bergizi Gratis sebagai Strategi Pembangunan Sumber Daya Manusia untuk Mendukung Pertahanan Negara - Sarjito, Aris (Asosiasi Ahli Administrasi Indonesia, 2024)
The free nutritious meal program is designed to improve the nutritional quality of school children and pregnant women as part of a strategic effort to build quality human resources (HR). The background of this study is based on the importance of public health as a non-military element that supports national resilience. This study aims to analyze the contribution of the free nutritious meal program to improving the quality of HR and examine the role of healthy HR in supporting the country's defense strategy. A qualitative approach with a descriptive-analytical method was used in this study, with secondary data including policy documents, program reports, and academic literature. The results of the study indicate that the free nutritious meal program has significant potential to improve the nutritional status, health, and productivity of school children and pregnant women. In addition, healthy HR plays an important role in supporting social stability, economic readiness, and national resilience holistically. The conclusion of the study emphasizes the importance of synergy between health and defense policies in creating a healthy, productive, and competitive young generation. Policy recommendations include strengthening infrastructure, improving coordination between agencies, and diversifying funding to ensure the sustainability of this program.